2005
DOI: 10.1002/jssc.200400027
|View full text |Cite
|
Sign up to set email alerts
|

A severe peak tailing of phosphate compounds caused by interaction with stainless steel used for liquid chromatography and electrospray mass spectrometry

Abstract: A severe peak tailing was observed for adenosine 5'-monophosphate in flow injection analysis with stainless steel tubing and water/methanol mixture (1:1, v/v) as carrier. The cause of the peak tailing was investigated by focusing on the chemical structure of the analytes, the material used for the analytical systems and the composition of the carrier. We clarified that the peak tailing was caused by the interaction between phosphate residues in the analytes and stainless steel. The severe peak tailing did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…The reduction of peak tailing by DEA was previously observed for nucleoside di-and triphosphates [9]. According to the literature, peak tailing results from interactions between phosphate compounds and stainless steel [22][23][24]. Therefore, triphosphate compounds are more affected than diphosphates and monophosphates [9].…”
Section: Optimization Of Liquid Chromatographymentioning
confidence: 68%
“…The reduction of peak tailing by DEA was previously observed for nucleoside di-and triphosphates [9]. According to the literature, peak tailing results from interactions between phosphate compounds and stainless steel [22][23][24]. Therefore, triphosphate compounds are more affected than diphosphates and monophosphates [9].…”
Section: Optimization Of Liquid Chromatographymentioning
confidence: 68%
“…By analogy, the same interaction is known to take place with nucleotides [31]. The analysis of nucleotides under typical RPLC conditions can result in severely tailed peaks, which is a result of the metal components contained within the wetted parts of chromatographic and electrospray systems [33][34][35]. In this study, adenosine (nucleoside), adenosine-monophosphate (AMP), adenosine-diphosphate (ADP) and adenosinetriphosphate (ATP) were chosen as model test compounds to probe the severity of these interactions in HILIC.…”
Section: Nucleotidesmentioning
confidence: 99%
“…Two groups extensively reported on the effect and concluded that it could, at least in part, be due to adsorption of phosphate groups to metal surfaces (Wakamatsu et al, 2005;Tuytten et al, 2006). Wakamatsu et al (2005) noticed extensive peak tailing when analyzing adenosine MP (AMP).…”
Section: Adsorption To Metalmentioning
confidence: 99%
“…Wakamatsu et al (2005) noticed extensive peak tailing when analyzing adenosine MP (AMP). The same effect was seen for guanosine MP (GMP) and uridine MP (UMP), but not for adenosine, guanosine, or uridine.…”
Section: Adsorption To Metalmentioning
confidence: 99%